Integrated Leaching of Cobalt Hydroxide Intermediate and Nickel-cobalt Sulfide Intermediate - Haikuo FU; Hengguan SHEN; Xitai ZHAO; Hengfu PENG; Hui DUAN; Yuli LIAO; Lingli ZHANG (Kuangchan zonghe liyong)
The integrated leaching of cobalt hydroxide intermediate and nickel-cobalt sulfide intermediate was studied. The experimental results show that the recovery of manganese in cobalt hydroxide intermediate and the utilization of nickel and cobalt sulfide intermediate were 99.92% and 90.65%, respectively, at the optimum conditions including quality ratio of cobalt hydroxide intermediate and nickel-cobalt sulfide intermediate of 1/5, initial acidity of reaction of 4 mol/L, reaction temperature of 70 ℃, liquid-solid reaction ratio of 3:1 and reaction time of 2.5 h. The residue could be used for leaching cobalt hydroxide intermediate as reductant. The objective of integrated leaching of cobalt hydroxide intermediate and nickel-cobalt sulfide intermediate was attained without the addition of any other oxygenant or reductant. Most importantly, the integrated process leaching is simple and feasible to operate and suitable for industrial production.